Cardiovascular remodeling and calcium-regulating function of parathyroid glands in arterial hypertension - B. G. Iskenderov; V. A. Lusov; L. F. Burmistrova; T. V. Lokhina; G. N. Abramova; N. A. Timofeeva (Российский кардиологический журнал)
In 95 patients with arterial hypertension (AH), left ventricular (LV) and brachial artery (BA) remodeling, as well as parathyroid hormone (PTH) level, was studied. Increased PTH level was associated with more prevalent and manifested LV and BA remodeling, and with decreased diastolic function and endothelium-depended vasodilatation. In 21,6% of AH patients, asymptomatic PTH hyper-secretion was registered. In these individuals, pathological types ofcircadian blood pressure profile were typical.